Staying Optimistic in the Middle of Academic Challenges: A Correlational Study of Optimism with Academic Resilience in Bidikmisi/KIP Students - Tri, Abayomi Maleakhi; Rahayu, Maria Nugraheni Mardi (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
Academic resilience is an individual's ability to increase academic success by being diligent, constantly reflecting, seeking appropriate help and having positive feelings in the midst of difficulties that occur. One of the factors that influences academic resilience is academic optimism, individuals must have clear goals and positive expectations for them when individuals want to have academic resilience. As a Bidikmisi/KIP College student, there are many challenges and demands that must be met to maintain a Bidikmisi/KIP scholarship until graduation. In all existing demands, a resilient attitude is needed so that students are strong in facing the demands of scholarships. One of the factors that influences academic resilience is optimism. The aim of this research is to determine the relationship between optimism and academic resilience of Bidikmisi/KIP students studying at Satya Wacana Christian University. The research method used is quantitative with a correlational design. The sample was obtained using an incidental sampling technique of 105 Bidikmisi/KIP Kuliah students. The research instrument used the Academic Resilience Scale (ARS-30) (α = 0.7) and Life Orientation Test-Revised (LOT-R) (α = 0.76). The analysis technique was carried out using Spearman rank correlation and obtained a correlation coefficient of 0.468. The results of the research show that there is a significant positive relationship between optimism and academic resilience in Bidikmisi/KIP students at Satya Wacana Christian University. Bidikmisi/KIP Kuliah students who have clear goals and strong confidence in their abilities are resilient in facing all existing demands and difficulties so that they are able to achieve academic success.Resiliensi akademik merupakan kemampuan individu untuk meningkatkan keberhasilan akademik dengan cara tekun, senantiasa berefleksi, mencari bantuan yang sesuai dan memiliki perasaan positif di tengah kesulitan yang menerpa. Salah satu faktor yang mempengaruhi resiliensi akademik adalah optimisme akademik, inidividu harus memiliki tujuan yang jelas dan ekspektasi yang positf terjadi pada mereka ketika individu ingin memiliki resiliensi akademik, Sebagai mahasiswa bidikmisi/KIP Kuliah, banyak tantangan dan tuntutan yang wajib dipenuhi untuk mempertahankan beasiswa bidikmisi/KIP Kuliah sampai lulus. Dalam segala tuntutan yang ada, diperlukan sikap yang resilien agar mahasiswa tangguh dalam menghadapai tuntutan beasiswa. Salah satu faktor yang memengaruhi resiliensi akademik adalah optimism. Tujuan penelitian ini adalah untuk mengetahui hubungan antara optimisme dengan resiliensi akademik mahasiswa bidikmisi/KIP Kuliah Universitas Kristen Satya Wacana. Metode penelitian yang digunakan adalah kuantitatif dengan desain korelasional. Sampel diperoleh dengan teknik insidental sampling sebanyak 105 mahasiswa bidikmisi/KIP Kuliah. Instrumen penelitian menggunakan Academic Resilience Scale (ARS-30) (α = 0,7) dan Life Orientation Test-Revised (LOT-R) (α = 0,76). Teknik analisis dilakukan dengan korelasi rank spearman dan diperoleh hasil koefisien korelasi sebesar 0,468. Hasil penelitian menunjukkan bahwa terdapat hubungan positif yang signifikan antara optimism dengan resiliensi akademik pada mahasiswa bidikmisi/KIP Kuliah Universitas Kristen Satya Wacana. Mahasiswa bidikmisi/KIP Kuliah yang memiliki tujuan yang jelas serta keyakinan yang kuat akan kemampuan dirinya, tangguh dalam menghadapi segala tuntutan dan kesulitan yang ada sehingga mampu mencapai kesuksesan akademik.